Effectiveness Implementation of Gagne's Learning Theory with Combination Problem-Solving Approach to Ability Think Critical Student - Tria Amalia; Wahyuni Suryaningtyas (Mathematics Education Journal, 2023)
21st century education requires students to have various abilities and skills including critical thinking. For this reason, it is necessary to apply learning theory in shaping students' thinking ability activities. This study aims to determine the effectiveness of learning mathematics through Gagne's Learning Theory with a combination of Problem Solvers at SMP Negeri 55 Surabaya. The subjects of this study were 36 students of class IX-E at SMP Negeri 55 Surabaya. The type of research used is quantitative descriptive research. Learning instruments and tools in learning used are lesson plans, worksheets, learning completeness results questions (test questions), student activity observation sheets, teacher ability observation sheets to manage learning, and student response questionnaires. The results of the study show that: (1) student activity during learning is in the active category; (2) the teacher's ability to manage abstract learning is very good; (3) Many students achieve 91% completeness with an average score of 3 for the indicator of critical thinking skills; and (4) student response to the learning process is very positive. The results of the study can be concluded that the application of Gagne's Learning theory with a combination of Problem Solving is effectively used in learning mathematics because it meets all the criteria for learning effectiveness.